2019
DOI: 10.1108/f-07-2018-0084
|View full text |Cite
|
Sign up to set email alerts
|

BIM for FM

Abstract: Purpose This paper aims to identify a generic set of information requirements for facilities management (FM) systems, which should be included in BIM as-built models for efficient information exchange between BIM and FM systems, and to propose a process to identify, verify and collect the required information for use in FM systems during the project’s lifecycle. Design/methodology/approach Both qualitative and quantitative approaches were applied at different stages of the study’s sequential design. The coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…To benefit, the design for maintenance should be considered in the early design phase [60,61]. Previously, it has also been found that specific information requirements for building information models to support FM systems are needed [62]. The study also confirms an earlier finding that facility managers can benefit from the advantages of BIM to enhance managing the significant amount of information [63].…”
Section: Previous Researchsupporting
confidence: 73%
“…To benefit, the design for maintenance should be considered in the early design phase [60,61]. Previously, it has also been found that specific information requirements for building information models to support FM systems are needed [62]. The study also confirms an earlier finding that facility managers can benefit from the advantages of BIM to enhance managing the significant amount of information [63].…”
Section: Previous Researchsupporting
confidence: 73%
“…We decided to synthesize the pyrrolo-pyrrolo(iso)quinolone skeleton through the 3+2 cycloaddition of azomethineylide as the 1,3-dipole. This strategy has been used widely to construct complex cyclic systems from relatively simple precursors [19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, as part of our ongoing research aiming at the design and synthesis of new fused N-heterocyclic compounds with biological activities [14][15][16][17][18], we present here the synthesis, structure and the antimicrobial evaluation of two series of compounds with pyrrolo-pyrrolo [2,1-a]isoquinoline and pyrrolo-pyrrolo [1,2-a]quinoline structures (fig. 1), both series having the end pyrrole cycle as N-substituted cyclic imide.…”
Section: Introductionmentioning
confidence: 99%
“…However, especially construction companies need to upgrade their technology in order to remain competitive and to use the new technical methods and tools in a targeted and benefits-oriented way (compare e.g. [65], [66], [67]). Ma et.…”
Section: Challenges For Data and Project Managementmentioning
confidence: 99%